Perancangan sistem pemantauan surat izin praktik (SIP) tenaga kesehatan di Dinas Kesehatan Kabupaten Pringsewu Provinsi Lampung - Faridz Ramadan; Eko Nugroho (Berita Kedokteran Masyarakat (BKM), 2017)
The design of monitoring system of health workers’ practice license in health office in Pringsewu LampungPurposeThe purpose of this study was to design a prototype of a monitoring system of health practice licenses (SIP) of health workers in Pringsewu’s local government. MethodsAn action research was conducted with 15 subjects. Data collection was done through in-depth interviews, observations and focus group discussions.ResultsBy order of priority issues, value urgency showed 70%, seriousness 75% and growth 75%, and the ultrasound matrix (urgency, seriousness and growth) showed that it is necessary to design a prototype monitoring SIP (100%), access to online or offline (66.66%), mapping of health workers (60%), and integration and communication with professional organizations and the Ministry of Health of Indonesia (60%). One of the functional testing systems that can be used is the SIP monitoring system. Furthermore, considering the system functional testing system the results showed 58% strongly agreed and 42% agreed with the use of the SIP designed monitoring system. The evaluation of the feasibility of the system shows that the aspect ratio before and after using the prototype was 5 times faster than before using the system. This system provides a positive effect on employee performance and can simplify management of managerial data licensing health professionals. ConclusionThe designed prototype system for monitoring practice licenses has overcome one of the problems in the regulatory process concerning the licensing of health personnel, although it is not developed fully, but the prototype is enough to give change and improved performance at the district health office in Pringsewu.